The crystal structure of poly[(μ 2-1-(1-imidazolyl)-4- (imidazol-1′-yl-methyl)benzene κ 2 N:N′)-(μ 2-3-nitrobenzene -1,2-dicarboxylato-k4,O,O′:O′′,O′′′]zinc(II)-κ 2, C21H15N5O6Zn - Li, Gui-Lian; Wu, Meng; Ma, Chen-Yang; Wang, Jing-Yi; Du, Yan-Han; Qi, Meng-Ni (Zeitschrift für Kristallographie. New crystal structures, 2025)
Zn, monoclinic, , = 9.3993(4) Å, = 22.8857(8) Å, = 9.8365(5) Å, = 103.658(5)°, = 2056.11(16) Å , = 4, ) = 0.0810, ) = 0.0856, T = 293(2) K.